1995
DOI: 10.1172/jci118132
|View full text |Cite
|
Sign up to set email alerts
|

Favorable left ventricular remodeling following large myocardial infarction by exercise training. Effect on ventricular morphology and gene expression.

Abstract: IntroductionContinued adverse remodeling of myocardium after infarction may lead to progressive ventricular dilation and heart failure. We tested the hypothesis that exercise training in a healed myocardial infarction-dysfunction rat model can favorably modify the adverse effects of ventricular remodeling including attenuation of abnormal myosin gene expression. Sprague-Dawley rats were subjected to either proximal LAD ligation or sham operation. At 5 wk after the operation, animals were randomly assigned to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 40 publications
7
82
0
1
Order By: Relevance
“…Then, in each dietary regimen, mice were assigned randomly to either a physical exercise protocol or to have no lifestyle modifications. Graduated physical exercise consisted of a progressive swimming program in a 1-m 2 surface area tank containing tap water 50 cm in depth and maintained at 23°C according to a protocol originally proposed by Orenstein et al (52). After preliminary pilot experiments (data not shown), to induce a graduated training, on the first day, the swimming time was 10 min in duration, and this time was then increased by 10 min each subsequent day (first week) until the maximum swim duration of 60 min was reached at the end of the second week.…”
Section: Methodsmentioning
confidence: 99%
“…Then, in each dietary regimen, mice were assigned randomly to either a physical exercise protocol or to have no lifestyle modifications. Graduated physical exercise consisted of a progressive swimming program in a 1-m 2 surface area tank containing tap water 50 cm in depth and maintained at 23°C according to a protocol originally proposed by Orenstein et al (52). After preliminary pilot experiments (data not shown), to induce a graduated training, on the first day, the swimming time was 10 min in duration, and this time was then increased by 10 min each subsequent day (first week) until the maximum swim duration of 60 min was reached at the end of the second week.…”
Section: Methodsmentioning
confidence: 99%
“…27 With this procedure, we obtained a rat model of AMI, whose mean infarct size was about 40% to 50% of the whole left ventricle ( Figure 2B). In this study, we found that PEDF was normally expressed in cardiomyocytes of LV tissues ( Figure 1C, sham) and that its levels in infarcted areas were decreased after LAD artery ligation ( Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…27 Briefly, male Sprague-Dawley rats (weighting about 300 g at 8 weeks of age; Charles River Breeding Laboratories, Yokohama, Japan) were anesthetized with intraperitoneal injections of ketamine hydrochloride (100 mg/kg b.wt.) and xylazine (5 mg/kg b.wt.).…”
Section: Rat Ami Modelmentioning
confidence: 99%
“…37,38 In rat models of cardiomyopathy, training has been reported to enhance chronotropic function, reverse detrimental variations in cardiac myosin gene expression and isozyme composition, attenuate ventricular dilation, and diminish wall tension within the heart. 39,40 Increases in oxidative enzyme activity and improvements in exercise-induced metabolic profiles within skeletal muscle have also been described. 41 If effective treatment of EPR dysfunction in heart failure proves a viable therapy for potentiating exercise tolerance, resultant augmentations in exercise capacity would enhance a patient's ability to tolerate physical training, potentially increasing the benefits derived from its prescription.…”
Section: Clinical Relevancementioning
confidence: 99%